A systematic and comprehensive review on low power wide area network: characteristics, architecture, applications and research challenges - Ass Diane; Ousmane Diallo; El Hadji Malick Ndoye (Discover Internet of Things)
Abstract The Internet of Things (IoT) has become a rapidly growing research field. This is due to the advancement of digital technologies, miniaturization, and the reduction of the cost of IoT devices and wireless connectivity, among others. Despite the plethora of technologies used for the Internet of Things, the trade-off between long data transmission range and low power consumption was not found until the advent of Low Power Wide Area Network (LPWAN) technologies. This paper reviews the main aspects of LPWANs and their technologies based on an exhaustive search in several online scientific databases, such as Springer, IEEE Xplore, the ACM digital library, and Google Scholar. This research methodology enabled us to gather recent work on LPWANs, which forms the basis of this article. It is informative and knowledge-updating support in the LPWANs’ environment that broadly covers LPWANs. This research work has developed the characteristics of LPWANs and the techniques used to achieve long-range energy efficiency, high scalability, and low cost. In addition, it presents the application areas of LPWAN technologies with use-case network architectures for each area, addresses spectrum and energy optimization, and discusses open research challenges that need to be focused to provide guidelines for further contributions.